PENDAPATAN DAN RISIKO BUDIDAYA UDANG VANAME DI KECAMATAN RAWAJITU TIMUR KABUPATEN TULANG BAWANG - Arum Renanda; Fembriarti Erry Prasmatiwi; Indah Nurmayasari (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2019)
This study aims to analyze income, risk and the relationship between income risk and vaname shrimp cultivation income.  This research was conducted in East Rawajitu Sub-district which was chosen purposively in February-March 2018.  There were 52 shrimp farmers, consisting of 27 farmers at Bumi Dipasena Utama Village and 25 farmers at Bumi Dipasena Agung Village. The data was analyzed by descriptive quantitative method using income analysis, R/C ratio, CV and Pearson product moment correlation.  The results showed that vaname shrimp cultivation in East Rawajitu subdistrict was profitable with R/C values >1.  The risk of vaname shrimp cultivation income in East Rawajitu subdistrict was high and there was a positive relationship between income risks with vaname shrimp cultivation income. Key words : profit, risk, vaname shirmp